Genetic knockout of NTRK2 by CRISPR/Cas9 decreases neurogenesis and favors glial progenitors during differentiation of neural progenitor stem cells - Roussel-Gervais, Audrey; Sgroi, Stéphanie; Cambet, Yves; Lemeille, Sylvain; Seredenina, Tamara; Krause, Karl-Heinz; Jaquet, Vincent (Frontiers in Cellular Neuroscience, 2023)
The tropomyosin receptor kinase B (TrkB) is encoded by the NTRK2 gene. It belongs to the family of transmembrane tyrosine kinases, which have key roles in the development and maintenance of the nervous system. Brain-derived neurotrophic factor (BDNF) and the neurotrophins NT3 and NT4/5 have high affinity for TrkB. Dysregulation of TrkB is associated to a large spectrum of diseases including neurodegeneration, psychiatric diseases and some cancers. The function of TrkB and its role in neural development have mainly been decrypted using transgenic mouse models, pharmacological modulators and human neuronal cell lines overexpressing NTRK2. In this study, we identified high expression and robust activity of TrkB in ReNcell VM, an immortalized human neural progenitor stem cell line and generated NTRK2-deficient (NTRK2 -/-) ReNcell VM using the CRISPR/Cas9 gene editing technology. Global transcriptomic analysis revealed major changes in expression of specific genes responsible for neurogenesis, neuronal development and glial differentiation. In particular, key neurogenic transcription factors were massively down-regulated in NTRK2 -/-cells, while early glial progenitor markers were enriched in NTRK2 -/-cells compared to NTRK2 +/+ . This indicates a previously undescribed inhibitory role of TrkB on glial differentiation in addition to its well-described proneurogenesis role. Altogether, we have generated for the first time a human neural cell line with a lossof-function mutation of NTRK2, which represents a reproducible and readily available cell culture system to study the role of TrkB during human neural differentiation, analyse the role of TrkB isoforms as well as validate TrkB antibodies and pharmacological agents targeting the TrkB pathway.